Shot noise and universal Fano factor as a characterization of strongly correlated metals - Yiming Wang; Chandan Setty; Shouvik Sur; Liyang Chen; Silke Paschen; Douglas Natelson; Qimiao Si (Physical Review Research)
Shot noise measures out-of-equilibrium current fluctuations and is a powerful tool to probe the nature of current-carrying excitations in quantum systems. Recent shot-noise measurements in the heavy-fermion strange metal YbRh_{2}Si_{2} exhibit a strong suppression of the Fano factor (F)—the ratio of the current noise to the average current in the dc limit. This system is representative of metals in which electron correlations are extremely strong. Here we carry out the first theoretical study on the shot noise of diffusive metals in the regime of strong correlations. A Boltzmann-Langevin equation formulation is constructed in a quasiparticle description in the presence of strong correlations. We find that F=sqrt[3]/4 in such a correlation regime. Thus, we establish the aforementioned Fano factor as universal to Fermi liquids, and we show that the Fano factor suppression observed in experiments on YbRh_{2}Si_{2} necessitates a loss of the quasiparticles. Our work opens the door to systematic theoretical studies of shot noise as a means of characterizing strongly correlated metallic phases and materials.